(untitled) (Bangladesh Journal of Nuclear Medicine, 2022)
Background: Radioiodine treatment in thyroidectomized differentiated thyroid carcinoma (DTC) patients was introduced in the world in 1940s and in Bangladesh in 1980. Long experience of treatment and lifelong follow up of DTC patients with proper documentation of medical records enriched the archive of the thyroid division of National Institute of Nuclear Medicine & Allied Sciences (NINMAS). Aims: To evaluate the response of radioiodine treatment in DTC patients at NINMAS and analyze the outcome and prognostic factors in this cohort of patients in a single institute of a developing country. Patients and Methods: This is a retrospective cohort study. A total of 7525 patients with DTC received RAI ablation therapy from 1980-2021 at NINMAS, among them 5448 patients were treated with radioiodine from 1980-2017. Data were obtained from the medical records of 3482 DTC patients who were followed up until 2021 and all relevant data were available. Demographical, histopathological, surgical, radioiodine ablation doses of 131I, serum biomarkers thyroglobulin (Tg), antithyroglobulin antibody (TgAb) and biochemical investigation data were analyzed systematically. Age, gender, tumor size, presence of local and distant metastases at presentation, extrathyroidal extension (ETE), disease recurrence, and cancer-specific survival were also evaluated. Risk stratifications for recurrence and staging were calculated for dosing of radioiodine. The single dose of radioiodine ranged from 30 mCi to 200 mCi was given according to the postsurgical risk assessment. Repeated doses of radioiodine were given in the cases of persistent disease (PD) and recurrent disease (RD). Results: The median age of DTC patients was 38 years, with a range of 5-87 years (39.90± 12.67 years), with the majority of patients falling within the 30-39 age group. The ratio of female to male was 3.74:1. Compared to the previous decade, patient number increased about 72 and 16-folds in relation to the 1980s and 1990s respectively at this institute. Papillary thyroid carcinoma (PTC) and follicular variant of thyroid carcinoma (FVPTC) together were evaluated in 3311(95.09%) cases and follicular thyroid carcinoma (FTC) was diagnosed in 171(4.91%). Excellent response (ER) was observed by a single dose of radioiodine ablation in 2853(81.94%) and PD and RD were noted in 388(11.14%) and 241(6.92%) respectively. Tg and TgAb levels at pre-therapy state were significantly higher in patients who had PD (P <0.000) and RD (P <0.000). Conclusion: Significant increase in the number of DTC patients was observed in the last two decades. ER was noted in 81.94% with a single dose of radioiodine. Serum Tg and TgAb are two prognostic factors for disease outcomes showing high Tg and TgAb in PD and RD cases. Bangladesh J. Nuclear Med. 25(2): 81-87, 2022